A Wide Spectrum of Autoimmune Manifestations and Other Symptoms Suggesting Immune Dysregulation in Patients With Cartilage-Hair Hypoplasia - Vakkilainen, Svetlana; Mäkitie, Riikka; Klemetti, Paula; Valta, Helena; Taskinen, Mervi; Husebye, Eystein Sverre; Mäkitie, Outi (Frontiers in Immunology, 2018)
Background: Mutations in RMRP, encoding a non-coding RNA molecule, underlie cartilage-hair hypoplasia (CHH), a syndromic immunodeficiency with multiple pathogenetic mechanisms and variable phenotype. Allergy and asthma have been reported in the CHH population and some patients suffer from autoimmune (AI) diseases. Objective: We explored AI and allergic manifestations in a large cohort of Finnish patients with CHH and correlated clinical features with laboratory parameters and autoantibodies. Methods: We collected clinical and laboratory data from patient interviews and hospital records. Serum samples were tested for a range of autoantibodies including celiac, anti-cytokine, and anti-21-hydroxylase antibodies. Nasal cytology samples were analyzed with microscopy. Results: The study cohort included 104 patients with genetically confirmed CHH; their median age was 39.2 years (range 0.6–73.6). Clinical autoimmunity was common (11/104, 10.6%) and included conditions previously undescribed in subjects with CHH (narcolepsy, psoriasis, idiopathic thrombocytopenic purpura, and multifocal motor axonal neuropathy). Patients with autoimmunity more often had recurrent pneumonia, sepsis, high immunoglobulin (Ig) E and/or undetectable IgA levels. The mortality rates were higher in subjects with AI diseases (χ(2)2 = 14.056, p = 0.0002). Several patients demonstrated serum autoantibody positivity without compatible symptoms. We confirmed the high prevalence of asthma (23%) and allergic rhinoconjunctivitis (39%). Gastrointestinal complaints, mostly persistent diarrhea, were also frequently reported (32/104, 31%). Despite the history of allergic rhinitis, no eosinophils were observed in nasal cytology in five tested patients. Conclusions: AI diseases are common in Finnish patients with CHH and are associated with higher mortality, recurrent pneumonia, sepsis, high IgE and/or undetectable IgA levels. Serum positivity for some autoantibodies was not associated with clinical autoimmunity. The high prevalence of persistent diarrhea, asthma, and symptoms of inflammation of nasal mucosa may indicate common pathways of immune dysregulation.